Anion exchange induced formation of kesterite copper zinc tin sulphide–copper zinc tin selenide nanoheterostructures. Issue 9 (2nd March 2021) - Yin, Deqiang; Li, Qi; Liu, Yang; Swihart, Mark T.
Abstract : Kesterite CZTS–CZTSe nanoheterostructures are synthesized by anion exchange in pristine kesterite CZTS nanostructures, which grow from cubic Cu9 S5 nanotemplates. Abstract : We report the colloidal synthesis of quaternary kesterite CZTS–CZTSe heterostructures via anion exchange reactions on a kesterite CZTS template. The crystal phase selectivity during the synthesis (kesterite vs. wurtzite) is due to the initial nucleation of cubic Cu9 S5 seeds, followed by incorporation of Zn and Sn. Upon injection of Se-precursor, which triggered simultaneous anion exchange and overgrowth of the pristine CZTS template, sandwich CZTS–CZTSe (core-tip) nanoheterostructures were obtained. X-ray photoelectron spectroscopy (XPS) and optical band gap measurement results suggest a change of intrinsic electronic structure of CZTS by Se-treatment. Our study not only provides insight into mechanisms of formation of kesterite CZTS nanocrystals (NCs) and subsequent anion exchange reactions, but also opens doors to access novel CZTSSe nanostructures for potential applications.